"Europe is dead" – on the philosophy of liberation of Enrique Dussel - Knežević, Višnja D. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
This paper discusses the idea of the Other in the works of the leading theoretician of the philosophy of liberation, Enrique Dussel. Although the philosophy of liberation is an authentic thought that establishes its principles in contrast to the fundamental propositions of European reflexive culture, the wider audience outside Latin America is little acquainted with it. It is a philosophy that analyzes the Other in a scope of dialectics of the center and periphery, relating the civilized and developed world to the idea of the first, and the rest of the world to the latter, for which the “first” one shows a direct and concrete interest. The practical sphere is brought into connection with the ontological one: the enslaved and exploited Other is marginalized to the periphery of being; in fact, he is made into non-being. His destruction is effected: as the one who is not me (multitude), the Other is at first made second-rated and thus less valuable (hierarchy) by the mere accidence of non being European (paradigm), only to be then easily thrown into non-existance, evened with nothingness (annihilation). Such an attitude implies an uncritical philosophy of domination, a particular imperial ontology, which is articulated as a hegemonic speech of (European) being and represents the theoretical completion of practical attitude toward the downtrodden Other. (Dussel accepts the Levinasian concept of the imperial character of Western thought). A special place is given to the fundamental subject of Modernity, the ego cogito, which on a practical level turns into an aggressive and annihilating ego conquiro of real historical and cultural oppression, being politically profiled through Homo homini lupus, and ontologically through polemos pater. Its certainty is self-certainity of the conquistador, the winning side in war, Lord – the Other is the pueblo, people. Resolution of the conflict, however, lies in the preference of neither the center nor the periphery, but in their dialectical mediation. However, according to Dussel's opinion, this neither should nor could prevent the articulation of an authentic voice and action of the Other, who autonomously creates his history and, in the place of Nietzsche, declares: Europe is dead.
Keywords: opposition; Europe/Latin America; ego cogito/ego conquiro; ontology; being/ non-being; Center-Periphery; The Other; E. Dusel